2014
DOI: 10.1007/s00167-014-3039-9
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of normative data on the knee rotatory profile and the usefulness of the Rotatometer, a new instrument for measuring tibiofemoral rotation: the reliability of the knee Rotatometer

Abstract: The results suggest the Rotatometer to be a simple and noninvasive device with high inter- and intra-observer reliability. The device can provide a normative rotational profile for reference purposes and thus can be used to determine the preoperative and postoperative rotational status of knees with anterior cruciate ligament injuries and compare results from different reconstruction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…26,31 However, our study is in line with in vivo results with regard to VV laxity and stiffness 8,9,27,30 and IE rotation laxity. 10,27,30 This is encouraging concerning the relevance of in vitro cadaveric testing of joint laxity. To our knowledge, the only cadaveric study to examine male-female differences in knee laxity and stiffness was by Hsu et al 12 Similar to our results, in response to a 134-N anterior tibial force, the results from Hsu et al indicated no male-female differences in AP joint laxity or stiffness at 0°and 30°of flexion.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…26,31 However, our study is in line with in vivo results with regard to VV laxity and stiffness 8,9,27,30 and IE rotation laxity. 10,27,30 This is encouraging concerning the relevance of in vitro cadaveric testing of joint laxity. To our knowledge, the only cadaveric study to examine male-female differences in knee laxity and stiffness was by Hsu et al 12 Similar to our results, in response to a 134-N anterior tibial force, the results from Hsu et al indicated no male-female differences in AP joint laxity or stiffness at 0°and 30°of flexion.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous in vivo studies have looked at male-female differences in knee laxity and stiffness. 3,[8][9][10]19,23,[26][27][28][29][30][31] In vivo findings related to AP laxity are conflicting; some report females to have greater laxity, 3,27,30 while other studies report no difference. 26,31 However, our study is in line with in vivo results with regard to VV laxity and stiffness 8,9,27,30 and IE rotation laxity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognise the significant difference between the absolute values of the two different measurement methods due to soft tissue movement over the bone and that the soft tissue in a cadaver which has been frozen and thawed will have different properties compared to that of a live subject. Similar experiments with Rotatometers/Rottometers using only live subjects with no skeletally mounted reference for comparison demonstrate high inter- and intra-observer reliability[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 75%
“…12 Existen maniobras cuantitativas para valorar la integridad del LCA, mediante el uso de instrumentos como el KT-1000 que cuantifica la maniobra de Lachman y el pivotshift meter que pretende cuantificar la maniobra de pivotshift. 13,14,15,16,17,18,19,20 Algunos otros dispositivos han sido utilizados para la medición del pivot-shift como sistemas electromagnéticos de rastreo, acelerómetros, sistemas de navegación y estudios imagenológicos. 16 Los sistemas electromagnéticos de rastreo has diferenciado cambios mínimos en la cuestión rotacional y detectado el pivot-shift; sin embargo, hay algunas condiciones que pueden alterar el resultado como: estructuras metálicas dentro de la sala de exploración, dispositivos electrónicos, la movilidad de tejidos blandos al realizar la maniobra.…”
Section: Introductionunclassified